Patient views on an electronic dispensing device for prepackaged polypharmacy: a qualitative assessment in an ambulatory setting - Allemann SS; Hersberger KE; Arnet I (Dove Medical Press, 2015)
Samuel S Allemann, Kurt E Hersberger, Isabelle ArnetPharmaceutical Care Research Group, Department of Pharmaceutical Sciences, University of Basel, Basel, SwitzerlandObjective: To collect opinions on medication management aids (MMAs) in general and on an electronic MMA (e-MMA) dispensing prepackaged polypharmacy in sealed pouches.Study setting: The setting involved community-dwelling older adults in Basel, Switzerland, in 2013.Study design: The study involved 1) a 14-day trial with the e-MMA and 2) a focus group to identify general attributes of MMAs, their applicability to the e-MMA, and possible target groups for the e-MMA.Data collection methods: Six participants using long-term polypharmacy and willing to try new technologies completed the 14-day trial and participated in the focus group. Inductive content analysis was performed to extract data.Principal findings: Participants rated ten of 17 general attributes as clearly applicable to the e-MMA and five as unsuitable. Attributes pertained to three interrelating themes: product design, patient support, and living conditions. Envisaged target groups were patients with time-sensitive medication regimens, patients with dementia, the visually impaired, and several patients living together to prevent accidental intake of the wrong medication.Conclusion: The evaluated e-MMA for prepackaged polypharmacy met the majority of the requirements set for an MMA. Patients' living conditions, such as mobility, remain the key determinants for acceptance of an e-MMA.Keywords: pharmaceutical care, medication adherence, medication management aids, automated drug dispensing